Flexibility. Developing effective movement - Sands, W. A.; McNeal, J. R. (Strength and conditioning for sports performance, 2016)
Aspects of flexibility development are often included in comprehensive strength and conditioning (S&C) programmes at the high school [33], collegiate [56] and professional levels [34], As an example, 100 per cent of Major League Baseball S&C coaches reported utilising flexibility training in their programmes [34], and 31 of 32 S&C coaches for rowing in the United Kingdom reported using some type of flexibility training [43]. While flexibility seems to be a consistent component of S&C programmes, the means and methods of developing this quality are reportedly quite varied, including both pre-practice and post-practice implementation. Coaches incorporate various static and ballistic proprioceptive neuromuscular facilitation (PNF) techniques, and dynamic stretching, for up to 10—15 minutes per session. The varied nature of reported use of flexibility exercises may indicate a lack of consensus, or that misconceptions persist regarding the benefits and role of such exercises in athlete development. Judge et al. [56] suggested that the possession of Certified Strength and Conditioning Specialist (CSCS) certification positively influenced the stretching practices chosen by collegiate S&C coaches, perhaps by providing up-to-date information about efficacious practices reported in research. Given that stretching for flexibility has been around for millennia, that it has widely practised and accepted measurement techniques, and that training methods appear to have changed little, one might think that flexibility is well understood. However, this assumption w ould be wrong, owing to a lack of a universally accepted conceptual and physiological framework, mechanisms, and test methods [50].